Enhancing University Students’ Emotional Intelligence and Self-Efficacy through Teaching Interventions - Nadya Nurhidayah Nurdin; Budiarti Putri Uleng; Nika Nurdiana (CV. Eureka Murakabi Abadi, 2025)
This study explores the impact of targeted teaching interventions on the development of emotional intelligence (EI) and self-efficacy among university students. Recognizing the critical role these psychological constructs play in academic success and personal well-being, the research implements a series of instructional strategies designed to foster emotional awareness, regulation, and confidence in academic and social contexts. Examines the efficacy of targeted interventions in enhancing Emotional Intelligence (EI) and Self-Efficacy (SE) by comparing pre-test and post-test scores across control and intervention groups, the study employ descriptive statistics revealed significant improvements in both constructs, with the intervention group demonstrating higher post-test means (EI: 80.32; SE: 77.38) compared to the control group (EI: 74.47; SE: 68.13). Normality and homogeneity tests confirmed the data’s suitability for parametric analyses, while independent samples t-tests indicated statistically significant differences between groups (p = 0.005 for both EI and SE). These findings align with foundational theories while highlighting the amplified effects of modern intervention strategies, such as digital tools and personalized training. Notably, SE exhibited greater malleability (mean difference = 9.25) than EI (mean difference = 5.85), challenging earlier assertions about EI’s rigidity. The study concludes that the value of structured interventions in fostering psychological competencies, but calls for longitudinal research to assess sustainability and investigations into moderating factors. Practical applications include integrating hybrid (digital-traditional) approaches in educational and organizational settings to maximize scalability and impact.